Consumers with unordered preferences - Uribe, Pedro (Estudios Económicos de El Colegio de México, 1996)
Theoretical research on consumer demand with nonordered and not necessarily convex preferences has been centered in the study of the equilibrium. This paper looks back at consumer as such, trying to reach substantive propositions, eventually refutable by empirical evidence. This paper explores the use of the outer gauge of preference sets, a “distance function”, with considerable success in the analysis of convex multiproduct technologies. In this paper, the gauge function is used to obtain comparative statistics equations based on the optimization of nonordered preference.